Recapitulation of various topologies and control strategies implicated in dynamic voltage restorer (DVR) for power quality improvement - Pal, Rakeshwri; Gupta, Sushma (International Journal of Engineering and Technology, 2018)
The fundamental desire of any power-driven industry is superior power quality of electrical supply for optimum exploitation of resources and smooth operation of equipment. However, some crucial problems such as sags, swells, harmonics and interruptions are documented as power quality issues. Out of those voltage sags and swells are generally found and take in a severe impact on the electrical equipment and thus ought to be compensated at an earliest to shun any mal-operation or crash. As an imperative solution to mitigate the voltage is-sues a custom power device (CPD), dynamic voltage restorer (DVR) is unanimously acquired. The DVR is a prominent CPD apparently recommended in the literature for the compensation of voltage sag and swell with a pro of active/reactive power management. A bulk vol-ume of literature reported on different configurations of DVR and different control technique utilized in it. This paper envelope detailed review on different feasible power circuit topologies and control techniques of DVR to anticipate power quality problems. The informative stuff coated in it articulates choice of control technique and power circuit ensuring the most advantageous performance of DVR in satisfy-ing the required quality of supply. Also, this paper delivers the valued information for the investigator of this province. Â Â Â